Influence of gelatin on structure and properties of polivinylacetate - Фабуляк, Г. Ф.; Масленнікова, Л. Д.; Смашнюк, Л. О. (Problems of Environmental Biotechnology, 2013)
The results of the analysis upramolecular structure polyvinylacetate-gelatin composition were given. Found that the change of gelatin’s content in polyvinylacetate bring about transformation occurring with micellar polyvinylacetate structures. The results of research make it possible to obtain new polymeric materials with prescribed properties.